2016
DOI: 10.19044/ejes.v3no3a4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Neurophobia: A Review Of The Current Pandemic And Proposed Educational Solutions

Abstract: Traditionally, the subject of neuroscience has been one of the most difficult courses for medical students in undergraduate medical education. Over the last few decades, a fear of neurology and the neurosciences, termed neurophobia, has presented among medical students around the world. Today, neurophobia has resulted in medical students not learning neurology and neurosciences to a sufficient extent to be able to apply this knowledge to patients presenting with neurologic symptomatology. To address the crisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Literature suggests that innovative pedagogical practices and instructional strategies must be adopted including blending of collective fields of digital technology (technology-enhanced learning [TEL]), brain-based education, adult and active learning theories, learning styles, and multiple intelligence theory. [ 46 47 48 49 ]…”
Section: P Romoting N Europhilia mentioning
confidence: 99%
“…Literature suggests that innovative pedagogical practices and instructional strategies must be adopted including blending of collective fields of digital technology (technology-enhanced learning [TEL]), brain-based education, adult and active learning theories, learning styles, and multiple intelligence theory. [ 46 47 48 49 ]…”
Section: P Romoting N Europhilia mentioning
confidence: 99%
“…However, there was no significant difference in OSCE scores between the two groups in the neurological examination, with the lowest average score of all grades. A study have shown that medical students have neurophobia, which has been demonstrated throughout the world, and neurology has the complex neurologic examination, difficult neuroanatomy and poorly taught neurology curricula [ 22 ]. Based on this we speculate that the interns were nervous about the high difficulty of neurological physical examination and the lack of teaching, which affected their assessment results.…”
Section: Discussionmentioning
confidence: 99%